BUCOVINA AS A TOURIST DESTINATION AND THE IMPACT OF THE RECENT INTERNATIONAL FINANCIAL CRISIS. RECOMMENDATIONS FOR A MODERN DESTINATION MANAGEMENT APPROACH IN INTERNATIONAL DESTINATION MARKETING - BÄHRE, Heike; FERGEN, Ulrike; CHASOVSCHI, Carmen (Revista de turism - studii și cercetări în turism, 2013)
Bucovina is a cultural landscape in the triangle bordered between the Ukraine, Romania and Moldova. Based on a theoretical planning approach in destination marketing management, Bucovina is to be regarded as a destination situated at the end of the involvement stage of the Tourism Area Life Cycle (TALC). Literature, internet research, qualitative interviews, and on site-observations depict Bucovina as a travel destination. The authors explore the impact of the financial crisis on Bucovina and forecast the destination trend for the next few years. Finally, they give recommendations for development of the Bucovina region in a sustainable, rapid and regulated manner.